Upregulation of Parkin Accelerates Osteoblastic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells and Bone Regeneration by Enhancing Autophagy and β-Catenin Signaling - Zhang, Wei; Hou, Weiduo; Chen, Mo; Chen, Erman; Xue, Deting; Ye, Chenyi; Li, Weixu; Pan, Zhijun (Frontiers in Cell and Developmental Biology, 2020)
Osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) plays a key role in bone formation. Parkin, an E3 ubiquitin ligase, related to Parkinson's disease and aging. Previous studies have indicated that Parkinson’s disease have a higher risk of osteoporotic fracture. Previous studies have indicated that Parkin is involved in the osteogenic differentiation of BMSCs. To investigate the effects and underlying mechanism of Parkin in the osteogenic differentiation of BMSCs, osteogenic differentiation was analyzed following upregulation or downregulation of Parkin. We found that Parkin was increased during differentiation. Parkin overexpression enhanced osteo-specific markers, and downregulation of Parkin mitigated osteo-specific markers. Moreover, upregulation of Parkin promoted β-catenin expression and autophagy and vice versa. The upregulation of β-catenin enhanced autophagy, and the activation of autophagy also increased the expression of β-catenin in Parkin-downregulated BMSCs. Parkin-overexpressed cell sheets accelerated bone healing in a tibial fracture model. Based on these results, we concluded that Parkin meditates osteoblastic differentiation of BMSCs via β-catenin and autophagy signaling.